2011
DOI: 10.1080/00379271.2011.10697724
|View full text |Cite
|
Sign up to set email alerts
|

Records of chironomids of the tribe Pentaneurini (Diptera: Chironomidae) in the Eastern Himalayas of India

Abstract: Abstract. Larva, pupa and female imago of Paramerina ampliseta n. sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This largely, because they are relatively difficult to rear in the laboratory, the typical generation period is relatively long, mutant variety is limited, chromosome maps are less complete and there is a lack of extensive knowledge of transmission genetic phenomena within the group. The wide range of morphological and ecological variation within the family, however, make the Chironomidae ideally suited for comparative studies in molecular and developmental genetics [62][63][64][65][66][67][68][69].…”
Section: Other Significant Aspects Of Chironomidaementioning
confidence: 99%
“…This largely, because they are relatively difficult to rear in the laboratory, the typical generation period is relatively long, mutant variety is limited, chromosome maps are less complete and there is a lack of extensive knowledge of transmission genetic phenomena within the group. The wide range of morphological and ecological variation within the family, however, make the Chironomidae ideally suited for comparative studies in molecular and developmental genetics [62][63][64][65][66][67][68][69].…”
Section: Other Significant Aspects Of Chironomidaementioning
confidence: 99%
“…Indeed, the Chironomidae are among the few insects living in the sea and the ocean [3,4]. Likewise, they occur in all continents where they have been found alive at heights of 5600 m on the glaciers of the Himalayas [5] and in the depths of the lakes [6]. Several qualitative observations showed that larvae of terrestrial Chironomidae are able to colonize the vegetation above the soil surface on heathlands [7].…”
Section: Introductionmentioning
confidence: 99%